The protective effect of Zataria multiflora Boiss. hydroalcoholic extract on TNF-α production, oxidative stress, and insulin level in streptozotocin-induced diabetic rats - marzieh mahmoodi; Farhad koohpeyma; Forough saki; Amir Maleksabet; mohammad Ali zare (Mashhad University of Medical Sciences, 2019)
Objective: Oxidative stress leads to reactive oxygen species (ROS) overproduction, which causes tissue injury in diabetic patients. The aim of this study was to evaluate the effects of Zataria multiflora extract on TNF-α, oxidative stress products, and insulin levels as well as lipid profile in diabetic rats. Materials and Methods: Rats were randomly divided into 6 groups of 10 animals. Diabetes was induced by a single injection of streptozotocin (STZ). Control and diabetic control rats orally received 1 mL/day of normal saline, whereas the other three groups received 250, 500 and 1000 mg/kg/day of Z. multiflora extract, and one non-diabetic group orally received 1000 mg/kg/day Z. multiflora extract, for 28 days. At the end of the treatment course, rats were anesthetized and their serum samples were analyzed for TNF-α, malondialdehyde (MDA), super oxide dismutase (SOD), total antioxidant capacity (TAC), lipid profile, total plasma protein, blood glucose, insulin, and liver enzymes levels. Results: Our results showed that cholesterol, LDL, TG, MDA and TNF-α levels decreased, but HDL, SOD, TAC, and total protein increased significantly in the diabetic group receiving 1000 mg/kg Z. multiflora compared to the diabetic control group (P